The PITX gene family as potential biomarkers and therapeutic targets in lung adenocarcinoma. Issue 4 (29th January 2021) - Zhang, Chunyi; Chen, Xing; Chen, Yefeng; Cao, Miaoying; Tang, Jixian; Zhong, Bo; He, Meng
Abstract : Abstract: The PITX gene family of transcription factors have been reported to regulate the development of multiple organs. This study was designed to investigate the role of PITXs in lung adenocarcinoma (LUAD). In this study, the transcriptional levels of the 3 identified PITXs in patients with LUAD were examined using the gene expression profiling interactive analysis interactive web server. Meanwhile, the immunohistochemical data of the 3 PITXs were obtained in the Human Protein Atlas website, and western blotting was additionally conducted for further verification. Moreover, the association between the levels of PITXs and the stage plot as well as overall survival of patients with LUAD was analyzed. We found that the mRNA and protein levels of PITX1 and PITX2 were higher in LUAD tissues than those in normal lung tissues, while those of PITX3 displayed no significant differences. Additionally, PITX1 and PITX3 were found to be significantly associated with the stage of LUAD. The Kaplan-Meier Plot showed that the high level of PITX1 conferred a better overall survival of patients with LUAD while the high level of PITX3 was associated with poor prognosis. Our study implied that PITX1 and PITX3 are potential targets of precision therapy for patients with LUAD while PITX1 and PITX2 are regarded as novel biomarkers for the diagnosis of LUAD.